Analisis Pendapatan Usahatani Buah Naga Di Desa Konarom Kecamatan Dumoga Tenggara Kabupaten Bolaang Mongondow - Geri Gein Fadila Aprilia Djogolang; Tommy F. Lolowang; Eyverson Ruauw (Sam Ratulangi University, 2022)
This research aims to analyze the income of dragon fruit farming in Konarom Village, Southeast Dumoga District, Bolaang Mongondow Regency, and analyze the feasibility of dragon fruit farming in Konarom Village, Southeast Dumoga District, Bolaang Mongondow Regency. The method used in this research is a survey method. The data used in this study are primary data and secondary data. Primary data was used through direct interviews using a questionnaire containing written questions to dragon fruit farmers, while secondary data was obtained from the village office and related agencies in this study with various literature on the internet. The data analysis method used in this research is descriptive analysis. The results showed that the land area of 3 dragon fruit farmers was 0.75-1 Ha. With total revenue is Rp. 516,750,000/Year. With a total cost of Rp. 144,189,000/Year, with the average amount of dragon fruit farming production is 11,483 Kg/Year. The income of dragon fruit farming in Konarom Village, Southeast Dumoga District, Bolaang Mongondow Regency is Rp. 372,561,000/Year. Judging from the value of the R / C ratio of 3.5. So it can be seen that dragon fruit farming is profitable and feasible to cultivate.